Exergo-sustainability behavior of high by-pass turbofan engine of a passenger aircraft during main flight phases - Aygun, Hakan (Taylor & Francis Inc, 2021)
In this study, thermodynamic analysis of PW4000 engine used in long-haul aircraft was carried out for eight flight phases. For this aim, energy, exergy, and exergo-sustainability metrics regarding the PW4000 were investigated for each phase. The main goal is to reveal differences between energetic and exergetic performance of flight phases using exergetic metrics. Also, exergetic behavior of six components of PW4000 was observed through flight phases. According to energy analysis, the overall efficiency of PW4000 was calculated as 33% at cruise phase, whereas its lowest value is observed as 8.7% at taxi-out phase. Considering component-based exergetic results, the combustor has the lowest exergy efficiency through flight phases. Namely, it changes between 77.55% and 88.66% with respect to flight conditions. It is followed by exergy efficiency of High Pressure Turbine (HPT) that resides between 87.07% and 89.61%. On the other hand, the exergy efficiency of the whole PW4000 has relatively high values at climb, cruise, and descent (CCD) phases. Namely, its value is estimated to be in the range of 32% and 36% at CCD phases. Besides, the wasted exergy ratio of the PW4000 varies from 28.37% at cruise phase to 49.01% at take-off phase. Finally, the exergetic sustainability index (ESI) of the PW4000 changes between 1 and 1.28 at CCD phases, whereas the lowest ESI belongs to taxi-out phase with 0.19. It is seemed that the current analysis may seem to help investigating optimum flight phases for the highest efficiency and thereby the lowest environmental impact.
Keywords: Turbofan engine; flight phases; exergy; thermodynamics